Pathways for maintenance of telomeres and common fragile sites during DNA replication stress - Özer, Özgün (Open Biol, 2018)
Oncogene activation during tumour development leads to changes in the DNA replication programme that enhance DNA replication stress. Certain regions of the human genome, such as common fragile sites and telomeres, are particularly sensitive to DNA replication stress due to their inherently ‘difficult-to-replicate’ nature. Indeed, it appears that these regions sometimes fail to complete DNA replication within the period of interphase when cells are exposed to DNA replication stress. Under these conditions, cells use a salvage pathway, termed ‘mitotic DNA repair synthesis (MiDAS)’, to complete DNA synthesis in the early stages of mitosis. If MiDAS fails, the ensuing mitotic errors threaten genome integrity and cell viability. Recent studies have provided an insight into how MiDAS helps cells to counteract DNA replication stress. However, our understanding of the molecular mechanisms and regulation of MiDAS remain poorly defined. Here, we provide an overview of how DNA replication stress triggers MiDAS, with an emphasis on how common fragile sites and telomeres are maintained. Furthermore, we discuss how a better understanding of MiDAS might reveal novel strategies to target cancer cells that maintain viability in the face of chronic oncogene-induced DNA replication stress.